Exposure to Cryptococcus neoformans var. gattii--a seroepidemiological study. - Seaton, R; Hamilton, A; Hay, R; Warrell, D (1996)
An enzyme-linked immunosorbent assay was developed to study prevalence of immunoglobulin G (IgG) antibody to non-capsular Cryptococcus neoformans var. gattii antigen in a population of healthy Papua New Guinea (PNG) controls and patients. Patients with acute C. neoformans var. gattii meningitis had elevated levels of IgG which declined significantly following treatment (P = 0.034). Levels in the sera of convalescent patients were significantly higher than those in PNG controls (P < 0.001), which in turn were significantly higher than in a UK control group (P < 0.001). Clear differences were observed amongst the PNG controls. Adults had significantly higher levels than children (P = 0.002) and men had significantly higher levels than women (P = 0.047). No difference was observed between levels in patient-related and unrelated controls. IgG responses in PNG controls mirror the prevalence of disease in this population. It is postulated that exposure to C. neoformans var. gattii is less common in children and women due to some as yet unidentified behavioural difference and that exposure occurs away from the home environment.